Praktik Ratib al-Haddad dan Pemaknaan Ayat Al-Qur’an: Studi Living Qur’an di Lingkungan Pesantren - Jaharuddin; Nasrullah; Fiddian Khairudin (Ta’wiluna: Jurnal Ilmu Al-Qur'an, Tafsir dan Pemikiran Islam, 2026)
This study aims to analyze the meanings of Qur’anic verses contained in Ratib al-Haddad and to examine how these verses are understood and internalized by students at Daarul Ishlah Asy-Syafi’iyyah Islamic Boarding School. This research employs a qualitative approach with a descriptive-analytical method within the framework of living Qur’an studies. Data were collected through observation, in-depth interviews, and documentation. The findings reveal that the practice of reciting Ratib al-Haddad has become a well-established spiritual tradition; however, students’ understanding of the Qur’anic meanings remains limited, resulting in predominantly ritualistic practices. The analysis demonstrates that the verses encompass theological, psychospiritual, and ethical-practical dimensions that have the potential to shape students’ religious consciousness in an integrative manner. This study highlights that Ratib al-Haddad functions not only as a devotional practice but also as a transformative Qur’anic educational instrument. Therefore, integrating devotional practices with thematic Qur’anic exegesis is essential to optimize the internalization of Qur’anic values in students’ daily lives.